The Role of Psychological Capital and Intragroup Conflict on Employees' Burnout and Quality of Service: A Multilevel Approach - Leon-Perez, Jose M.; Antino, Mirko; Leon-Rubio, Jose M. (Frontiers in Psychology, 2016)
Previous studies have found a negative association between intragroup conflict and both employees’ health and performance, including the quality of service that employees provide. However, some authors have indicated that such negative effects of intragroup conflict depend on how conflict is managed. In addition, at individual level, research is increasingly emphasizing the role of psychological strengths (i.e., psychological capital) as predictors of health and performance. Thus, this research addresses both a main effect at individual level (psychological capital on burnout/quality of service) and a moderated cross-level model (2-2-1: intragroup conflict, conflict management climate and burnout/quality of service) in a cross-sectional survey study (N = 798 workers nested in 55 units/facilities). Results revealed a main effect of psychological capital on both burnout (r = -.50) and quality of service (r = .28). Also, there was an association between intragroup relationship conflict and burnout (r = .33). Finally, there was an interaction effect in which conflict management climate buffers the negative association between intragroup conflict and quality of service. Practical implications of these results for developing positive and healthy organizations that prevent potential psychosocial risks at group level while promote individual strengths are discussed.